Kinerja Pemberdayaan Gender dalam Aspek Keselamatan - Devi Ratnasari; Lucky Bindri; Tedy Herdian (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The purpose of this study is to test and understand the effect of Investigator Accountability and Gender Empowerment on Performance of the Investigation Team. According to National Transportation Safety Committee, gender equality has become an important issue in development because socially it has differenciate roles, responsibilities, rights and functions as well as the activities of men and women in society. These differences ultimately make people tend to be discriminatory and picky about the treatment of access, participation, and control in the results of development of men and women including in the field of transportation and accident investigation. This research was using quantitative analysis methods with multiple regression analysis tools with a sample size of 40 respondents, calculated the relationship between the accountability of investigators along with gender empowerment on the performance of the investigation team. The results of the study: there is a positive relationship between Investigator Accountability and the Performance of the Investigation Team of the National Transportation Safety Committee as well as Gender Empowerment. And this also applies to the positive relationship between Investigator Accountability and Gender Empowerment together with the Performance of the National Transportation Safety Committee's Investigation Team. This research is not only useful to improve policy making in the field of human resource development in the National Transportation Safety Committee but also in other institutions that have the same scope.